1993
DOI: 10.1021/bi00078a008
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of chicken liver dihydrofolate reductase: Binary thioNADP+ and ternary thioNADP+.cntdot.biopterin complexes

Abstract: The role of the 3'-carboxamide substituent of NADPH in the reduction of pteridine substrates as catalyzed by dihydrofolate reductase (EC 1.5.1.3, DHFR) has been investigated by determining crystal structures at 2.3 A of chicken liver DHFR in a binary complex with oxidized thionicotinamide adenine dinucleotide (thioNADP+) and in a ternary complex with thioNADP+ and biopterin. These structures are isomorphous with those previously reported for chicken liver DHFR [Volz, K.W., Matthews, D.A., Alden, R.A., Freer, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…This single atom substitution relative to NADP ϩ can result in altered binding characteristics in nucleotide-binding proteins (51,52,66), and it may also cause larger absorbance shifts near 510 nm (50, 67). 4 We encountered some difficulty with excessive equilibration/stabilization times for the FMN ox/sq couple during oxidative titrations of eNOSr.…”
Section: Purification and Properties Of Enosr And Nnosr-mentioning
confidence: 99%
“…This single atom substitution relative to NADP ϩ can result in altered binding characteristics in nucleotide-binding proteins (51,52,66), and it may also cause larger absorbance shifts near 510 nm (50, 67). 4 We encountered some difficulty with excessive equilibration/stabilization times for the FMN ox/sq couple during oxidative titrations of eNOSr.…”
Section: Purification and Properties Of Enosr And Nnosr-mentioning
confidence: 99%
“…However, when these two proteins are loaded with thio-NADP ϩ , the carbothiamide group of the analogue in both cases is twisted relative to the plane of the pyridine ring, although the twist has the opposite sense: X am is Ϫ160°in DHFR and ϩ140°in dIII. The increased twist of the carbothioamide group in DHFR was suggested to avoid unfavorable contact between the sulfur atom and the CH group at position 4 of the pyridine ring (20). It was noted to be less than in a model compound, 2-methyl-4(thiocarbamoyl)-pyridine (47).…”
Section: Discussionmentioning
confidence: 99%
“…It was noted to be less than in a model compound, 2-methyl-4(thiocarbamoyl)-pyridine (47). McTigue et al (20) concluded that a larger rotation in DHFR is prohibited by the binding site geometry of the protein and that the unfavorable interactions between the CH group of pyridine ring and the S atom are not completely relieved. The oppositely directed twist of the carbothiamide group in dIII (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations